The Role of Buddhi Dharma University Academics in the Cultural Preservation of Kebaya House - Lianah The; Limajatini Limajatini; Ruby Santomoko; Dian Anggraeni; Etty Herijawaty (Edumaspul: Jurnal Pendidikan, 2025)
The purpose of this study is to find out the extent of the role of the academic community of Buddhi Dharma University in preserving the culture of Rumah Kebaya as a form of participation in the procession of the celebration of the 12th anniversary of the Toa Pek Kong. This 12-year procession is a Chinese tradition at the Boen Tek Bio (BTB) Temple, Tangerang City. The Chinese Kebaya House is different from the Betawi Kebaya House. It is called Rumah Kebaya because this house has a roof shape that resembles a folded saddle and when viewed from the side the folds look like kebaya folds. Some of the remaining Kebaya Houses have undergone restoration due to the needs of their residents and developments over time. The research methods used are qualitative analysis, phenomena and ethnography, through in-depth interviews, direct observation, and documentation. The statements of five owners of traditional houses in Tangerang City can provide a conclusion about how important it is to preserve old houses as historical relics.